2018
DOI: 10.1021/acs.nanolett.7b04728
|View full text |Cite
|
Sign up to set email alerts
|

Direct Mapping of Phase Separation across the Metal–Insulator Transition of NdNiO3

Abstract: Perovskite rare-earth nickelates RNiO are prototype correlated oxides displaying a metal-insulator transition (MIT) at a temperature tunable by the ionic radius of the rare-earth R. Although its precise origin remains a debated topic, the MIT can be exploited in various types of applications, notably for resistive switching and neuromorphic computation. So far, the MIT has been mostly studied by macroscopic techniques, and insights into its nanoscale mechanisms were only provided recently by X-ray photoemissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 30 publications
4
53
1
Order By: Relevance
“…The detailed growth conditions can be found in previous references 20,25 . Following the NNO film deposition, a PMMA A6 resist soft-mask was prepared with e-beam lithography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed growth conditions can be found in previous references 20,25 . Following the NNO film deposition, a PMMA A6 resist soft-mask was prepared with e-beam lithography.…”
Section: Methodsmentioning
confidence: 99%
“…where full G corresponds to the full heating curve obtained from the experiment, and D is the dimension of our system set to be 2. This two-dimensional approximation seems reasonable since the film thickness is only ~4 nm 23 and the size of M-phase domains is about two orders of magnitude higher 19,20 . In Fig.…”
Section: Jhl and Ft Contributed Equally To This Workmentioning
confidence: 97%
“…When these electronic phases compete, they segregate at nano-or mesoscopic length scales, giving rise to complex, multiscale domain textures [4][5][6]. Nowadays, there is overwhelming evidence of domain pattern formation for an array of emergent phenomena, including metal-insulator transitions [7][8][9][10][11], charge/magnetic ordering [12][13][14], and unconventional superconductivity [15][16][17]. Several studies have identified these spatial textures as essential underpinnings for novel phenomena in TMOs and other correlated electron [5,13,[18][19][20][21].Rare earth nickelates (RENiO 3 ) are a fertile platform to realize and explore the emergent physics brewing in proximity to electronic symmetry-breaking phenomena, thanks to the cooperative action of the coupled charge, spin, and lattice degrees of freedom.…”
mentioning
confidence: 99%
“…More details on the interface growth and specimen preparation can be found in Ref. 21. Atomically-resolved EELS mapping was performed on a Nion UltraSTEM 200 microscope operated at 100 keV.…”
Section: Appendix: Methodsmentioning
confidence: 99%